Thismia perlisensis (Thismiaceae), a new red-annulus Thismia species from Peninsular Malaysia - Besi, Edward Entalai; Jabar, Qistina Anis Mad; Rahman, Syamil Abd; Saad, Mohd Zulkifly; Ahmadni, Ag Shaffie Ag; Go, Rusea (Phytotaxa, 2024)
A new species, Thismia perlisensis, found during a scientific expedition in the Perlis State Park, is described and illustrated. The new species was discovered in a wetland forest on a limestone foothill. Morphological description, photographic data including habitat, and a key to the species of the Thismia Sect. Thismia Subsect. Brunonithismia recorded from Malaysia are provided. The new species is easily distinguished from the similar species, T. arachnites, T. javanica, T. tentaculata, and T. kenyirensis by the prominent reddish dome-shaped annulus instead of ring-like with rim, deeply trilobed stigma with bifid and subulate lobes, and claviform apices of the inner tepals.